CLINICAL CHARACTERISTICS OF NON-PROTEINURIC KIDNEY DISEASE IN PATIENTS WITH TYPE 2 DIABETIC IN INDIA: A COHORT STUDY. - Nayak, Bapu; Satpathy, Anurag (Student's Journal of Health Research Africa, 2024)
Background The study aims to examine the clinical profile and progression of non-proteinuric diabetic kidney disease (NP-DKD) in type 2 diabetic patients in India and compare it with proteinuric diabetic kidney disease. Methods A cohort study of 120 patients over 18 years old was carried out. Individuals were divided into proteinuric (n=68) and non-proteinuric (n=52) groups based on uPCR or 24-hour urine protein levels. Data on demographics, clinical parameters, and biochemical investigations were gathered at baseline and during follow-ups at six months and one year. Renal function was assessed using eGFR, and proteinuria was monitored. Statistical analyses were performed. Results The study comprised 70 males (58.3%) and 50 females (41.7%). The participants had a mean age of 55.3 ± 10.2 years and an average diabetes duration of 12.5 ± 6.4 years. The proteinuric group exhibited a significantly lower baseline eGFR (45.8 ± 12.6 ml/min/1.73 m²) compared to the nonproteinuric group (62.4 ± 8.7 ml/min/1.73 m², p < 0.001). Over one year, the proteinuric group had a larger mean decline in eGFR (8.5 ± 3.4 ml/min/1.73 m²) than the nonproteinuric group (4.2 ± 2.1 ml/min/1.73 m², p < 0.001). ACEi/ARB therapy substantially reduced proteinuria in the proteinuric group (p < 0.01). Hyperkalemia was more prevalent in the proteinuric group (22.1%) compared to the nonproteinuric group (7.7%, p = 0.03). Conclusion NP-DKD poses a significant risk for renal function decline, similar to proteinuric DKD. ACEi/ARB therapy effectively reduces proteinuria but needs careful monitoring for hyperkalemia. Early detection and tailored management are crucial for improving NP-DKD patient outcomes. Recommendations Regular monitoring of renal function and proteinuria, along with the use of ACEi/ARB therapy, should be considered for all diabetic patients, with particular attention to those with NP-DKD. Further research is ought to explore additional therapeutic options and improve diagnostic techniques for NP-DKD.